Effects of continuous positive airway pressure on blood pressure in obstructive sleep apnea patients: The Apnea Positive Pressure Long‐term Efficacy Study (APPLES). (14th November 2019) - Javaheri, Sogol; Gottlieb, Daniel J.; Quan, Stuart F.
Summary: Obstructive sleep apnea is associated with hypertension, and short‐term studies have demonstrated a modest reduction in blood pressure with continuous positive airway pressure therapy. We evaluated the effects of continuous positive airway pressure versus sham continuous positive airway pressure on blood pressure in 1, 101 participants with obstructive sleep apnea from the Apnea Positive Pressure Long‐term Efficacy Study, a randomized, sham‐controlled double‐blinded study designed to assess the impact of continuous positive airway pressure on neurocognition. Participants with apnea−hypopnea index ≥ 10 were randomly assigned to continuous positive airway pressure or sham continuous positive airway pressure. Blood pressures measured in the morning and evening at baseline, 2 months and 6 months were analysed post hoc using a mixed‐model repeated‐measures analysis of variance. The largest magnitude reduction was approximately 2.4 mmHg in morning systolic pressure that occurred at 2 months in the continuous positive airway pressure arm as compared with an approximate 0.5 mmHg reduction in the sham group (continuous positive airway pressure effect −1.9 mmHg, p  = .008). At 6 months, the difference between groups was diminished and no longer statistically significant (continuous positive airway pressure effect −0.9 mmHg, p  = .12). Sensitivity analysis with use of multiple imputation approaches to account for missing data did not change the results. Treatment with continuous positive airway pressure for obstructive sleep apnea reduces morning but not evening blood pressure in a population with well‐controlled blood pressure. The effect was greater after 2 than after 6 months of treatment.